Efektivitas Penggunaan Media Sosial dalam Pemasaran Restoran: A Literature Review - Bakar, Nurunnisa Paquita Syech Abu (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Social networking sites (SNS) have penetrated the daily lives of many people, with an estimated more than 4 billion SNS users in 2021. Currently, many restaurants use social media as a promotional tool. Many customers share their dining experiences and interact with other customers on social media. It is important for restaurant management to pay attention to the quality, message argumentation, and aesthetics of the uploaded content in order to create an emotional connection between customers and the restaurant. In order to create an effective social media strategy, it is necessary to identify and determine the platforms that suit your restaurant. This research was carried out using a qualitative approach and a literature review method for articles published in 2019 - 2023. Sources of research articles regarding the use of social media marketing in the restaurant industry were obtained by searching using the keyword